-9x+3+5x=2x-3x+3+7-2

Simple and best practice solution for -9x+3+5x=2x-3x+3+7-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9x+3+5x=2x-3x+3+7-2 equation:


Simplifying
-9x + 3 + 5x = 2x + -3x + 3 + 7 + -2

Reorder the terms:
3 + -9x + 5x = 2x + -3x + 3 + 7 + -2

Combine like terms: -9x + 5x = -4x
3 + -4x = 2x + -3x + 3 + 7 + -2

Reorder the terms:
3 + -4x = 3 + 7 + -2 + 2x + -3x

Combine like terms: 3 + 7 = 10
3 + -4x = 10 + -2 + 2x + -3x

Combine like terms: 10 + -2 = 8
3 + -4x = 8 + 2x + -3x

Combine like terms: 2x + -3x = -1x
3 + -4x = 8 + -1x

Solving
3 + -4x = 8 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
3 + -4x + x = 8 + -1x + x

Combine like terms: -4x + x = -3x
3 + -3x = 8 + -1x + x

Combine like terms: -1x + x = 0
3 + -3x = 8 + 0
3 + -3x = 8

Add '-3' to each side of the equation.
3 + -3 + -3x = 8 + -3

Combine like terms: 3 + -3 = 0
0 + -3x = 8 + -3
-3x = 8 + -3

Combine like terms: 8 + -3 = 5
-3x = 5

Divide each side by '-3'.
x = -1.666666667

Simplifying
x = -1.666666667

See similar equations:

| -x-2y+z=-6 | | 3x/7-5=4 | | 9(x-1)+3x=-9x+5 | | 2x+4y-2z=6 | | 0.42x-5=4 | | x+3y-z=12 | | 5x-y+5z=30 | | 5x-2x+6-4+14=5x-3x+8 | | 3(g-7)-2=4 | | 16=-4-4x | | -x+2y-3z=-9 | | -3t+5=26 | | 4x-2x+3-8=7x-5+4x | | 3t+5=26 | | (x^2+y^4)(x^2-y^4)=0 | | 0.67x+7=21 | | 72+36=0 | | 5x-2+8=7x-4 | | 21=8x-75 | | 6a+5x=36 | | (4s+4)(4s-4)=0 | | 3x+y+z=14 | | (3r-1)(4r-3)=0 | | 15-8m=73 | | -8x+6x-7x=3x(4-3)-5x-15 | | 98p=197 | | 5/3= | | 170-2x=25x+20 | | -5=15+4x | | 5x-x+3=-x+7 | | 5-9x=37-16x | | 3n+4=56 |

Equations solver categories